2005
DOI: 10.1111/j.0142-5463.2005.00265_3.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel ‘permanent’ acid‐type hair color made possible with dye–metal ion complex technology

Abstract: The advantages and disadvantages of oxidative permanent and acid‐type semi‐permanent hair colors are evident. The former provides a long‐lasting ‘permanent’ color, while the latter imparts less damage to the hair. We developed a novel acid‐type hair color technology that can allow an acid dye and a metal ion to form a complex inside the hair similar to the oxidative hair color. It is well known that acid dye diffuses into the hair and creates an ionic bond with the positively charged amino acid residues of hai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Permanent dyes essentially last until new hair growth appears, which is every 4-6 weeks for the average consumer [3,11,12]. Dyes that are less permanent tend to be larger and adsorb onto the surface of hair [13] or diffuse only into the cuticle, or the outermost region of the hair fiber [11]. The precursors that give rise to permanent hair dyes are capable of diffusing into the cortex (an inner region of the hair fiber), due to their small size, where they react to form oligomers that aggregate and become too large to be desorbed from the hair [2,4,5,12].…”
Section: Overview Of the Dyeing Of Human Hairmentioning
confidence: 99%
See 2 more Smart Citations
“…Permanent dyes essentially last until new hair growth appears, which is every 4-6 weeks for the average consumer [3,11,12]. Dyes that are less permanent tend to be larger and adsorb onto the surface of hair [13] or diffuse only into the cuticle, or the outermost region of the hair fiber [11]. The precursors that give rise to permanent hair dyes are capable of diffusing into the cortex (an inner region of the hair fiber), due to their small size, where they react to form oligomers that aggregate and become too large to be desorbed from the hair [2,4,5,12].…”
Section: Overview Of the Dyeing Of Human Hairmentioning
confidence: 99%
“…The precursors that give rise to permanent hair dyes are capable of diffusing into the cortex (an inner region of the hair fiber), due to their small size, where they react to form oligomers that aggregate and become too large to be desorbed from the hair [2,4,5,12]. In each case, some dye can remain adsorbed onto the surface of hair [11,13]. Dye adsorbed onto the surface or within the outer layers of hair can more easily be removed upon shampoo treatment [1,4,5,[9][10][11], especially if dye is weakly bound and the cuticle is damaged (more porous).…”
Section: Overview Of the Dyeing Of Human Hairmentioning
confidence: 99%
See 1 more Smart Citation
“…Ochiai et al [60] reported that permanent dyes can be developed in hair using dye-metal ion complexes. These scientists used aluminum chloride as the metal ion which was allowed to penetrate into the hair so that the aluminum ion could complex with the acid dyes in the hair.…”
Section: Novel Permanent Dye Using a Dye-metal Ion Complexmentioning
confidence: 99%
“…Wool dyeing is very different from hair dyeing because of the high temperatures involved in the former. In fact, low temperature dyeing in wool is [80][81][82][83][84][85] C. Solvent assist dyeing permits wool to be dyed at [60][61][62][63][64][65][66][67][68][69][70] still too high a temperature for dyeing human hair. Prototype systems have been developed based on chemistry related to that of natural melanin pigment formation [10].…”
mentioning
confidence: 99%